2006
DOI: 10.1038/sj.jcbfm.9600199
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Uptake and Metabolism of α-[11C]Methyl-l-Tryptophan in Human Brain Tumors

Abstract: Abnormal metabolism of tryptophan has been implicated in modulation of tumor cell proliferation and immunoresistance. a-[ 11 C]Methyl-L-tryptophan (AMT) is a PET tracer to measure cerebral tryptophan metabolism in vivo. In the present study, we have measured tumor tryptophan uptake in 40 patients with primary brain tumors using AMT PET and standard uptake values (SUV). Tryptophan metabolism was further quantified in 23 patients using blood input data. Estimates of the volume of distribution (VD 0 ) and the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 70 publications
3
126
0
Order By: Relevance
“…Nevertheless, the high 18 F-FETrp uptake in the bladder and pancreas suggests that this tracer would not allow visualization of tumors in these organs because of high background activity. Despite the differences in distribution, both tracers demonstrated similarly low and continuous brain accumulation, suggesting that 18 F-FETrp will be suitable for the imaging of intracranial brain tumors as previously established with 11 C-AMT (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Radiation Dosimetry For 18 F-fetrpmentioning
confidence: 79%
See 2 more Smart Citations
“…Nevertheless, the high 18 F-FETrp uptake in the bladder and pancreas suggests that this tracer would not allow visualization of tumors in these organs because of high background activity. Despite the differences in distribution, both tracers demonstrated similarly low and continuous brain accumulation, suggesting that 18 F-FETrp will be suitable for the imaging of intracranial brain tumors as previously established with 11 C-AMT (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Radiation Dosimetry For 18 F-fetrpmentioning
confidence: 79%
“…Our previous PET studies demonstrated differential 11 C-AMT transport and trapping in human gliomas, lung cancer, and breast cancer, tumors that expressed both the L-type amino acid transporter 1 and IDO1 (23,26,(45)(46)(47). However, the widespread use of 11 C-AMT for cancer imaging is not feasible because of its short half-life and tedious radiosynthesis.…”
Section: Radiation Dosimetry For 18 F-fetrpmentioning
confidence: 99%
See 1 more Smart Citation
“…Uyttenhove et al (2003) showed that a majority of human tumors constitutively express IDO. Another study demonstrated that gliomas and glioneuronal tumors have an elevated TRP uptake and metabolism (Juhasz et al, 2006). This high TRP metabolism by low-grade tumors is very likely to be associated with an activation of the kynurenine pathway, which represents a mechanism regulating tumor cell growth and persistence (Juhasz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…6 We have previously demonstrated tryptophan metabolism in a variety of human brain tumors using α-[ 11 C]methyl-l-trypto phan (AMT) positron emission tomography (PET) imaging. [7][8][9][10] AMT is an amino acid radiotracer, which can measure expression and activity of indoleamine 2,3-dioxygenase (IDO), the first and rate-limiting step of the kynurenine pathway of tryptophan catabolism, can enable tumor cells to effectively evade the host's immune response. The potential role of this system was investigated in meningiomas.…”
Section: Introductionmentioning
confidence: 99%